Improvement of neurocognitive function in responders to an antiviral therapy for chronic hepatitis C. Issue 2 (24th June 2013) - Kraus, Michael R.; Schäfer, Arne; Teuber, Gerlinde; Porst, Heiner; Sprinzl, Kathrin; Wollschläger, Sven; Keicher, Christian; Scheurlen, Michael
<x xml:space="preserve">Abstract</x> Earlier studies have suggested neurocognitive impairment in patients with chronic hepatitis C virus (HCV) infection even before liver cirrhosis has developed. Since these deficits might be reversible after successful antiviral therapy, we analyzed the long‐term course of neurocognitive parameters in HCV patients with and without successful virus elimination by an interferon‐based antiviral treatment. In a multicenter study including 168 HCV patients receiving antiviral therapy (peginterferon alpha‐2b and ribavirin) we performed a long‐term follow‐up of neurocognitive performance before and after treatment. Neurocognitive function was psychometrically assessed using the computer‐aided TAP (Test Battery of Attentional Performance). When tested at least 12 months after termination of antiviral treatment, patients with sustained virologic response (SVR) had improved significantly as compared to their pretreatment performance in three of five TAP subtasks (vigilance, P < 0.001; shared attention: optical task, P < 0.001; working memory, P < 0.001). Patients who failed to eradicate the virus, however, showed no significant long‐term changes in neurocognitive performance in all five subtasks assessed (0.194 < P < 0.804). In the posttreatment evaluation, neurocognitive function was significantly better in responders to the antiviral therapy as compared to nonresponders. Conclusion: Successful eradication of HCV leads to a significant improvement of relevant aspects of attentional and neurocognitive performance, indicating that the neurocognitive impairment caused by chronic HCV infection is potentially reversible. This therefore suggests an added therapeutic benefit of antiviral treatment in HCV infection. Improvement of neurocognitive function may be an additional treatment indication in patients with HCV. (HEPATOLOGY 2013;58:497–504)